Embedding smart energy technology in built environments: A comparative study of four smart grid demonstration projects. Issue 7 (November 2015) - Skjølsvold, Tomas Moe; Ryghaug, Marianne
The smart grid has become important in energy discussions. Inspired by science and technology studies (STS), this article compares four smart grid demonstration projects that engage households in Norway, where much activity has been triggered by a mandatory roll-out of smart electricity meters by 2019. We ask how local actors across different sectors interpret the potential of smart electricity meters, and how different understandings lead to diverging innovation strategies. The result is four case studies illustrating how smart grid set-ups are constructed, and how new smart technologies are socialized into pre-existing localities or not. The four case studies highlight: (1) a constellation of healthcare and the electricity industry, resulting in a focus on simplicity and welfare. (2) A merger between the construction industry and the electricity industry, exploring how passive houses, PV-systems and smart technology influence collective practices. (3) How local authorities, research and industry interpreted smart grids differently, resulting in a focus on "greening", grid optimization and user flexibility. (4) How organizational and disciplinary conflicts led to alienation from the smart grid concept, hindering socialization. This diversity within a small country suggests that smart grids should be treated as situated technology rather than a "catch-all" silver bullet.